Indium sulfide thin films as window layer in chemically deposited solar cells - Lugo Loredo, Shadai; Peña Méndez, Yolanda; Calixto Rodriguez, María Estela; Messina Fernández, S.; Alvarez Gallegos, Alberto; Vázquez Dimas, Alejandro; Hernández García, Tomás Constantino (North-Holland, 2014)
Indium sulfide (In2S3) thin films have been synthesized by chemical bath deposition technique onto glass substrates using In(NO3)3 as indium precursor and thioacetamide as sulfur source. X-ray diffraction studies have shown that the crystalline state of the as-prepared and the annealed films is β-In2S3. Optical band gap values between 2.27 and 2.41 eV were obtained for these films. The In2S3 thin films are photosensitive with an electrical conductivity value in the range of 10−3 –10−7 (Ω cm)−1, depending on the film preparation conditions. We have demonstrated that the In2S3 thin films obtained in this work are suitable candidates to be used as window layer in thin film solar cells. These films were integrated in SnO2:F/In2S3/Sb2S3/PbS/C–Ag solar cell structures, which showed an open circuit voltage of 630 mV and a short circuit current density of 0.6 mA/cm2.